The two muwashshahed granddaughters of Dalia Ibn Asim Al-Gharnati A study in poetic formation (Journal of the College of Basic Education, 2022)
The paper studies reproduction in the Muashahat Grand daughters of Alghirnati's Dalli'ia. The paper aims at examining the poetic formation of these two Muashahat Grand Daughters-the Green Muashahat and the Red Muashahat the poet reproduces from the Grand Daughters of his Dalli'ia- the Green، the Noni'ia، the Red and the Lami'ia. Ibn Assim Alghirnati wrote his two reproduced Muashahats using a new ink but not the black which was typical for him. He wrote the first in the green ink and it became green and he used the simple or Ragis metre. Its form consists of three lines، The first of these is an amatory opening while the second and the third lines are eulogistic praising Sultan Yousif Bin Nasir.Ibn Assim wrote the second Muashahat in the red ink، thus it becomes red. He wrote it using the Ragis or the quick metre. Its form consists of the three lines، the first of the these is amatory opening as in the previous Green Muashahat while the second and the third are eulogistic of Sultan Yousif Bib Nasir. As far as contents are concerned، the two Green and red Muashahats، which are the Grand Daughters، are also eulogistic of the Sultan Abi Alhajaj Yousif Bin Nasir. In this regard، they are like the Mother Dalli'ia and the Grand Daughters-the Green، the red، the Noni'ia and the Dalli'ia. Thus، the character of Bin Nasir becomes the main interest of the poet in the two Muashahat Grand Daughters.